2014
DOI: 10.12988/ams.2014.43247
|View full text |Cite
|
Sign up to set email alerts
|

System dynamics modelling and its implications for childhood obesity prevention: evidence from improving the consumption of portion size and meal frequency

Abstract: The childhood obesity has rapidly increased, though little is known about the impact of frequency of meals and portion size on weight and obesity. The objective of this study is to compare and to determine the effective strategy for obesity prevention by improving the consumption of portion size and meal frequency. This study utilised the secondary data obtained from the Health Survey for England for the child population aged between 2 to 15 years in United Kingdom 3284 Norhaslinda Zainal Abidin et al.This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…An alternative method to quantify the contents of systems maps for decision making and intervention design are stock and flow diagrams [45], which have been applied to population health problems [46] [47]. Conversion of CLDs to stock and flow models, however, relies on assumptions and development of mathematical equations for elements in the model.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative method to quantify the contents of systems maps for decision making and intervention design are stock and flow diagrams [45], which have been applied to population health problems [46] [47]. Conversion of CLDs to stock and flow models, however, relies on assumptions and development of mathematical equations for elements in the model.…”
Section: Discussionmentioning
confidence: 99%
“…All 17 included studies were published in the last decade and eight were set in the United States (US). Seven studies included children, adolescents and adults, separating them into age cohorts where each age group transferred to the next cohort over time 46–52 ; seven articles examined children and adolescent populations 47,53–58 . Three studies investigated adolescents only 59–61 .…”
Section: Resultsmentioning
confidence: 99%
“…At the intrapersonal behavioral level, the simulation model on portion size and meal frequency was used to test whether the British target set for childhood OW/OB by 2020 could be reached. 53,54 They concluded that it could only be reached by 2026, but did not specify the interventions which could change the portion size and meal frequency. The simulation model on social transmission of OW/OB analyzed the effect on social transmissions of all combinations (n = 15) of prevention and treatment interventions targeting adults or children.…”
Section: Intervention Testing and Leverage Points For Ow/ob Preventionmentioning
confidence: 99%
See 2 more Smart Citations